2018
DOI: 10.1111/trf.14886
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of platelet counts in two hematology analyzers and potential effects on prophylactic platelet transfusion decisions

Abstract: The XN-2000 fluorescent PLT counting method showed excellent correlation with the CD61 reference count, closely followed by the CELL-DYN Sapphire optical method. XN-2000 impedance and optical and Sapphire impedance methods are not accurate enough for basing transfusion decisions on. Only XN-2000 fluorescent, Sapphire optical, and CD61 methods are sufficiently accurate for making appropriate clinical decisions in patients with severe thrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…However, if the RBC or platelet size histograms are abnormal or if the platelet count is below a preset limit, the PLT‐F method is performed as a reflex test to improve accuracy by clearly distinguishing platelets from other blood cells 11 . The performance of XN‐PLT‐F focusing on accurate detection of low platelet counts was evaluated in several studies 1,11‐13 . These studies reported that XN‐PLT‐F was a reliable method for low platelet counting and was preferred method to make appropriate decisions regarding platelet transfusions in thrombocytopenic patients, which was consistent with our result.…”
Section: Discussionsupporting
confidence: 86%
“…However, if the RBC or platelet size histograms are abnormal or if the platelet count is below a preset limit, the PLT‐F method is performed as a reflex test to improve accuracy by clearly distinguishing platelets from other blood cells 11 . The performance of XN‐PLT‐F focusing on accurate detection of low platelet counts was evaluated in several studies 1,11‐13 . These studies reported that XN‐PLT‐F was a reliable method for low platelet counting and was preferred method to make appropriate decisions regarding platelet transfusions in thrombocytopenic patients, which was consistent with our result.…”
Section: Discussionsupporting
confidence: 86%
“…The prophylactic transfusion threshold in low-risk patients is generally considered to be 10 or 20 × 10 9 /L, 1-3 making the accuracy of the PLT count by automated hematology analyzers a fundamental issue for physicians to provide effective care. [4][5][6] Despite significant advancements in PLT enumeration accuracy and precision, 7 approximately two-third of hematology analyzers have been shown to overestimate the PLT concentration in thrombocytopenic…”
mentioning
confidence: 99%
“…red cell "ghosts") in the scatterplot of cell size (forward light scatter) vs. RNA content (fluorescence intensity). The XN-series also shows improved precision of platelet counts below 50 × 10 9 /L and better correlation (r 2 ≥ 0.80) with the flow cytometric reference method for platelet enumeration due to a 5 times larger sample volume analyzed [24,27,28,[30][31][32]. This progress in the XN-series may account for the moderate correlation of IPF between the XE-2100 and the XN-2000 (r 2 ≥ 0.60) [24,27] and potentially improves the utility of IPF especially in hematological patients with very low platelet counts and in clinical settings with interference of aberrant cell populations and debris (e.g.…”
Section: Automated Determination Of Reticulated Plateletsmentioning
confidence: 93%